2015
DOI: 10.3109/13880209.2015.1024330
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of atractylenolide I on systemic inflammation in the mouse model of sepsis created by cecal ligation and puncture

Abstract: Objective: Our present study is designed to investigate the protective effect of AT-I on systemic inflammation in the mouse model of sepsis created by cecal ligation and puncture (CLP), and explore the possible mechanism. Materials and methods: Sepsis mouse model was established by CLP, and the tested dosages of AT-I were 10, 20, and 40 mg/kg (ip). Pro-inflammatory cytokines in serum (TNF-a, IL-1b and IL-6) were determined by the ELISA method; serum lipopolysaccharide (LPS) level was measured by the Limulus Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 26 publications
(33 reference statements)
2
20
0
Order By: Relevance
“…Of note, the elevation of hippocampal IL-1β levels in mice subjected to CUMS was partly reversed by treatment with AT-I for 3 weeks. Previous studies have indicated that AT-I exhibited anti-inflammatory activity and inhibited the production of IL-1β (15,29), which is consistent with the ELISA results for IL-1β of the present study. In addition, it was previously demonstrated that IL-1β activates the neurotransmitters 5-HT and NE in the CNS (30).…”
Section: Discussionsupporting
confidence: 82%
“…Of note, the elevation of hippocampal IL-1β levels in mice subjected to CUMS was partly reversed by treatment with AT-I for 3 weeks. Previous studies have indicated that AT-I exhibited anti-inflammatory activity and inhibited the production of IL-1β (15,29), which is consistent with the ELISA results for IL-1β of the present study. In addition, it was previously demonstrated that IL-1β activates the neurotransmitters 5-HT and NE in the CNS (30).…”
Section: Discussionsupporting
confidence: 82%
“…The occurrence of sepsis and consequent MOF is highly associated with bacteria and endotoxin translocation, which can trigger excessive inflammatory response and organ dysfunction [15]. LPS is the main components of the cell wall of Gram-negative bacteria and many studies proved that LPS could induce lethal inflammatory response, causing MOF and even death [9, 16]. Correspondingly, removal of LPS in animals was effective in treatment of sepsis [16].…”
Section: Discussionmentioning
confidence: 99%
“…LPS can promote overexpression of proinflammatory cytokines including IL-6, IL-1 β , and TNF- α , which was involved in subsequent sepsis [18, 19]. It was previously found that TNF- α played a pivotal in sepsis which could initiate systematic inflammatory response [9]. IL-6 is also associated with CLP induced sepsis, and it was reported that selective blockade of IL-6 transsignaling improves survival rate [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atractylodes macrocephula Koidz (A. macrocephula, also known as Baizhu), an important component in traditional Chinese herb medicine, have been shown to be beneficial for the treatment of variety of diseases including cancers by regulating various molecules and pathways [7-10]. Atractylenolide 1 (ATL-1), one of major bioactive compounds of Atractylodis macrocephalae, has anti-inflammatory and anti-tumor activities [8, 10-12].…”
Section: Introductionmentioning
confidence: 99%